EFFECT OF OIL PRICE SHOCKS ON NIGERIA’S MACROECONOMIC VARIABLES - Bello, Buhari; Saheed, Zakari; Muktar, Mustapha; Egwaikhide, Chris; Oyeniran, Wasiu (African Journal of Social and Behavioural Sciences, 2025)
The performance of macroeconomic variables in Nigeria has been strongly associated with the oil sector. The oil price shocks have a significant impact on a number of critical macroeconomic factors, including the exchange rate, inflation rate, oil revenue, and government expenditure, to name a few. The objective of this paper is to investigate and analyse the effect of oil price shocks on selected macroeconomic variables in Nigeria using time series techniques of the Non-linear Autoregressive distributed Lags (NARDL) model. The oil price and macroeconomic variables data were collected for the periods of 42 years (1981 – 2022) from the Central Bank of Nigeria and the US Energy Information Administration (EIA). The Bound Test of the NARDL specification suggests the presence of cointegration among variables. The results show that in the short-run and long-run, oil price shocks have a significant effect on macroeconomic variables such as exchange rate, inflation rate, oil revenue and government expenditure. The effect of global oil price shocks on inflation rate is positive, indicating that an increase in oil price leads to an increase in inflation rate in Nigeria; in contrast, the effect of shocks in the oil price on exchange rate is negative, indicating that an increase in global oil price leads to depreciation of exchange rate and fall in oil revenue thereby affecting government expenditure negatively in Nigeria. Hence, the study recommends that appropriate measures such as functional refineries and stable macroeconomic policies should be emphasized by the Nigerian government.